Answer: the first one is 14 and the second one is 5
Step-by-step explanation:
Answer:
2
Step-by-step explanation:
Use rise over run (y2 - y1) / (x2 - x1)
Plug in the points:
(6 + 6) / (2 + 4)
12/6
= 2
So, the rate of change is 2
Answer:
8. yes, ASA
9. yes, SAS
10. yes, AAS
11. no
12. no
13. yes, SSS
Step-by-step explanation:
we have
(a+b)(3a-b)(2a+7b)
step 1
Solve
apply distributive property
(a+b)(3a-b)=3a^2-ab-3ab-b^2=3a^2-4ab-b^2
step 2
Multiply (3a^2-4ab-b^2) by (2a+7b)
6a^3+21a^2b-8a^2b-28ab^2-2ab^2-7b^3=6a^3+13a^2b-30ab^2-7b^3
answer is
<h2>6a^3+13a^2b-30ab^2-7b^3</h2>
Cross multiply
2x(3x-4) = 3(x+2)
5x - 8x = 3x + 6
-3x= 3x+6
x = 6
I think